Real-time quality control for chemical and biotechnological processes: a brief review - Kołodziejczak-Radzimska, Agnieszka; Rukowicz, Beata; Davin, Sharon (Journal of Medical Science, 2023)
Monitoring critical process parameters of chemical and biotechnological processes is an essential tool at every stage of drug manufacturing technology. The aim of Process Analytical Technology (PAT) is to provide effective tools, such as multidimensional data analysis, modern analytical methods, and monitoring tools, for the continuous improvement of process understanding and knowledge. Among the methods of wide interest are optical and spectroscopic techniques that can be used in the control of chemical and biotechnological processes. The selection of the appropriate method is crucial and depends on many factors, including the nature of the process, the number of variables, and analytical limitations. This review focuses on a brief and precise characterization of spectroscopic and optical methods that can be applied to monitoring and control of chemical and biotechnological processes.
Keywords: Process Analytical Technology (PAT); Real-Time Process Control; Online Analysis; Monitoring Techniques